フロンによる南極上空のオゾン層破壊説の検証(その1 疑問点について) - 山下, 正和; 12362; ヤマシタ, マサカズ; 9000002429656; Yamashita, Masakazu; 20113102 (同志社大学理工学研究所, 2007)
本論文は、「フロンガスによるオゾン層破壊」説に対する疑問点について述べている。ノーベル賞受賞者がキーポイントとして指摘している文中のFig.4(a)では、オゾンが分解して生成するとされているClOが増加しているのに、オゾンの量が減少しているようには見えない。Fig,(a)と(b)からは、ClOの生成とオゾンの分解は無関係にみえる。 This paper presents questions about the theory of ozone layer disruption by chlorofluorocarbon (CFC).In the article, Fig. 4 (a), which a Nobel Prize winner mentioned as a key point, shows an increase in the level of C10, which is considered as a decomposition product of ozone, but no apparent decrease in the amount of ozone.Figs. 4 (a) and (b) indicate no relationship between C10 production and ozone decomposition. application/pdf departmental bulletin paper